Evaluating learning and teaching technologies in further education - Ann Jones; Jane Barnard; Judith Calder; Eileen Scanlon; Julie Thompson (Association for Learning Technology, 2000)
There is currently an unprecedented interest in the use of technologies for supporting teaching and learning. In post-compulsory education, the current Government's commitment to increasing access to Lifelong Learning is expressed through a number of initiatives that also affect the further education (FE) sector. For example, in The Learning Age: A Renaissance for a New Britain (Stationery Office, 1998) the government outlines its proposal to expand the scale, scope and nature of both further and higher education. The Learning Age follows a number of such government papers that emphasize the importance of Information and Communication Technologies (ICTs) or Information and Learning Technologies (ILTs) in FE and HE.